PDE9 Inhibitor PF-04447943 Attenuates DSS-Induced Colitis by Suppressing Oxidative Stress, Inflammation, and Regulating T-Cell Polarization - Rana, Mohammad Nasiruddin; Lu, Jie; Xue, Enfu; Ruan, Jingjing; Liu, Yuting; Zhang, Lejun; Dhar, Rana; Li, Yajun; Hu, Zhengqiang; Zhou, Jie; Ma, Wangqian; Tang, Huifang (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a form of inflammatory bowel disease, which manifests as irritation or swelling and sores in the large intestine in a relapsing and remitting manner. In a dextran sulfate sodium sulfate (DSS)-induced UC model in female mice, we found that the levels of cyclic guanosine monophosphate (cGMP) are reduced, while the expression of phosphodiesterase 9A (PDE9A) is highest among all phosphodiesterase (PDEs). Since PDE9 has the highest affinity toward cGMP, we evaluated the selective PDE9 inhibitor PF-04447943 (PF) as a potential candidate for UC treatment. PF has been extensively studies in cognitive function and in sickle cell disease, but not in models for inflammatory bowel disease (IBD). Therefore, we used female C57BL/6 mice treated with 3% DSS alone or co-treated with PF or sulfasalazine (SASP) to study the body weight, colon length, histopathology, and measure superoxide dismutase (SOD), malondialdehyde (MDA), and cGMP level, as well as cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-17 (IL-17), interleukin-12/23 (IL-12/23), interleukin-10 (IL-10), and pathways including nuclear factor kappa B (NF-κB), signal transducer and activator of transcription 3 (STAT3), and inflammasome activation. In addition, the number of dendritic cells (DC) and regulatory T cells (Treg cell) was assessed in the spleen, lymph node, and colon using flow cytometry. DSS reduced the number of goblet cells, decreased colon lengths and body weights, all of them were attenuated by PF treatment. It also suppressed the elevated level of inflammatory cytokines and increased level the anti-inflammatory cytokine, IL-10. PF treatment also reduced the DSS-induced inflammation by suppressing oxidative stress, NF-κB, STAT3, and inflammasome activation, by upregulating nuclear factor erythroid 2-related factor 2 (Nrf-2) and its downstream proteins via extracellular signal-regulated kinase (ERK) phosphorylation. Importantly, PF reversed imbalance in Treg/T helper 17 cells (Th17) cells ratio, possibly by regulating dendritic cells and Treg developmental process. In summary, this study shows the protective effect of a PDE9A inhibitor in ulcerative colitis by suppressing oxidative stress and inflammation as well as reversing the Treg/Th17 cells imbalance.